The quantum mechanics of many-body systems. - Thouless, D. J. (Pure and applied physics, 1961)
The Quantum Mechanics of Many-Body Systems provides an introduction to that field of theoretical physics known as """"many-body theory."""" It is concerned with problems that are common to nuclear physics, atomic physics, the electron theory of metals, and to the theories of liquid helium three and four, and it describes the methods which have recently been developed to solve such problems. The aim has been to produce a unified account of the field, rather than to describe all the parallel methods that have been developed; as a result, a number of important papers are not mentioned. The main